Analytic hierarchy process method for minimize negative sustainability and environmental impacts - Jakaria, R.B.; Widodo, H.; Haizal, N.; Ibrahim, M.B. (2020)
The concept of economic linearity that is, take, make, and discard, is no longer relevant in product design, this is due to product design must meet economically, safely and reliably shown by looking at the attributes inherent in the product, which aims to make customers feel satisfied, buy go back and recommend the product. However, with the increasing number of products that are not environmentally friendly it is necessary to minimize the negative impact of sustainability in designing products that require a recovery phase. This study aims to determine the effect of sustainable product design in minimizing the negative impacts caused by attitudes and behaviors that are influenced by the environment. The analysis technique uses PLS . warp. and the Process Hierarchy Analysis (AHP) method. The results of the design of this research product have a direct influence on the impact of negative sustainability with a parameter coefficient of .. This means, sustainable product design is carried out, must pay attention to the negative impacts caused, then test the factors that are more dominant relationships between variables using AHP that produces. The most dominant factor in testing the sub-criteria that influence product design in Minimizing the Impact of Negative Sustainability, from the results of tests that have been done, then the behavior of the Environment with a value of . is the conclusion that in designing the product in order to minimize the negative impact of the influence due to the conditions used in Sustainable product design, the influence of human environmental behavior on the environment becomes a major factor.